ARCHAEOLOGIES OF HITLER'S ARCTIC WAR heritage of the Second World War German military presence in Finnish Lapland. - Seitsonen, Oula. ([S.l.] : ROUTLEDGE, 2020)
This book discusses the archaeology and heritage of the German military presence in Finnish Lapland during the Second World War, framing this northern, overlooked WWII material legacy from the nearly forgotten Arctic front as dark heritage' - a concrete reminder of Finns siding with the Nazis, often seen as polluting war junk' that ruins the pristine natural beauty' of Lapland's wilderness. The scholarship herein provides fresh perspectives to contemporary discussions on heritage perception and ownership, indigenous rights, community empowerment, relational ontologies and also the ongoing worldwide refugee crisis.
1. Introduction; Part I. Hitler's Arctic War and its Material Remains; 2. Why an Archaeological Study of the Second World War?; 3. Finnish-German Waffenbrüderschaft: The Northern Brothers-in-arms, 1940-1945; Part II. Strangers in a Strange Land: Germans and their Prisoners in an Alien Arctic Landscape; 4. Soldiers' and Prisoners' Places and Landscapes; 5. Soldiers' and Prisoners' Things and Materiality; 6. Entangled with the North: Placelessness, Disorder and Dislocation; Part III. Ignored, Yet Remembered: Post-war Significance of the German WWII Remains; 7. Heritage Past, Present and Future; 8. Materialities of a Haunting Past -- or Present?; 9. Positive Uses for a Haunting and Difficult Past; 10. Custodians of "War Junk": Local and Global Heritage of Second World War in Lapland
OCLC-licensed vendor bibliographic record.
Keywords: World War, 1939-1945 -- Lapland -- Antiquities; Military archaeology -- Lapland; Prisoners of war -- Lapland; World War, 1939-1945 -- Prisoners and prisons, German; World War, 1939-1945 -- Social aspects -- Lapland; Cultural property -- Lapland; Collective memory -- Lapland; Lapland -- Antiquities; HISTORY / General; HISTORY / Military / World War II; HISTORY / Europe / Scandinavia